Clinical impressions of juvenile homicide offenders - Garbarino, James (The Routledge international handbook of juvenile homicide, 2024)
Developmental psychologist James Garbarino has evaluated over 100 juvenile homicide offenders (JHOs) at various times in the justice process, including prior to their conviction and decades later in terms of resentencing hearings. In this chapter, Dr. Garbarino describes the nature of his evaluations and highlights the characteristics of these JHOs in terms of demographics and adverse childhood experiences. He shares his observations from his involvement in dozens of resentencing hearings of JHOs in the context of the US Supreme Court’s decision in Miller v. Alabama (2012). He discusses rehabilitation and transformation in the context of sentence length, juveniles’ accounts of their growing up, juveniles’ vulnerability to false confessions, and informed consent in relation to bad choices. Takeaway points from Dr. Garbarino’s chapter include his reliance on research to argue that the characteristics of the murders committed by juveniles are not predictive of “incorrigibility” decades later. He makes recommendations for sentence length that are based on developmental maturity and outcome studies of JHOs. Based on scientific evidence, he concludes his chapter by maintaining that rehabilitation should be the “default option” in JHO resentencing cases.